The effect of using a proposed training device in developing some kinematic variables and achieving discus throwing for the disabled, class (54) - Abdulkareem Hameed, Rajaa; khamees Jaber, Khalid; Hamid Khamees, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The importance of this study came to shed light on the importance of the proposed device, which includes improving the motor path of the disc in the throwing mode (force mode) and throwing, as well as improving and developing the special strength and development of the muscles working in these two important stages and helping to develop kinematic variables related to skill performance and correct mechanical conditions. It has to add integration in developing the technical performance of discus throwing and achieving outstanding achievement for this category of disabled people under study category (54). The study aimed to design a proposed device for throwing the disc for the disabled category (54) and to identify the effect of training on this device in developing some kinematics and achievement for throwing the disc for the disabled category (54). The research sample was chosen in the intended way, from the players of the Paralympic Sub-Committee in Diyala in Athletics for the Disabled in the event of throwing the disc, class (54), and their number is (8) players; (2) players were excluded for the purposes of pilot experiments, as the research sample became (8). The research sample constituted 80% of the original research community, and the research procedures included conducting design and manufacturing procedures for the proposed device, as well as conducting reconnaissance experiments, tribal and dimensional tests, and measuring the kinematic variables, which included starting angle, direction angle, attack angle, starting speed, and point height. Launching, angular and circumferential velocity of the aiming arm, and acceleration obtained). The exercises were applied using the training device for a period of (8) weeks and at a rate of (3) training units per week and The total number of training units was (24) units during the duration of the experiment, as the number of training units reached (24) units, and the time of the total training unit was (90) minutes. The main section, and the researchers concluded that the exercises on the proposed device led to the development of the special force, the kinematic variables under research, and achievement for the members of the research sample. Researchers emphasize the use of the (manufactured device) as an aid to develop the special strength of discus throwers, especially the disabled class (56), as well as emphasizing explosive and rapid strength training, which is included in the development of achievement, and conducting exercises on the proposed device according to the motor paths of the technical stages of the disc.